2007
DOI: 10.1097/01.ogx.0000271138.31234.d7
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Exposure to DES: Lessons Learned … Future Concerns

Abstract: The short- and long-term effects of the widespread use of diethylstilbestrol (DES) over 3 decades have become a distant memory for many clinicians. Others are too young to remember the flurry of activity in the early 1970s on the part of many medical centers to identify the offspring of women who were prescribed DES during their pregnancies. This medication was given in an attempt to prevent multiple pregnancy-related problems such as miscarriage, premature birth, and abnormal bleeding. The recognition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 26 publications
0
39
0
1
Order By: Relevance
“…The damage incurred by the exposure may not be immediate and may only be manifested in adulthood or during aging. The consequences may be apparent even in subsequent generations and the classic example is the cases of vaginal carcinoma in daughters of mothers who were exposed to DES during their pregnancies (Herbst et al, 1999;Anway & Skinner, 2006;Rubin, 2007). The susceptibility of an individual may vary due to genetic polymorphism and so the results of the same exposure could be different.…”
Section: Pesticides As Endocrine Disrupting Chemicals (Edc)mentioning
confidence: 99%
“…The damage incurred by the exposure may not be immediate and may only be manifested in adulthood or during aging. The consequences may be apparent even in subsequent generations and the classic example is the cases of vaginal carcinoma in daughters of mothers who were exposed to DES during their pregnancies (Herbst et al, 1999;Anway & Skinner, 2006;Rubin, 2007). The susceptibility of an individual may vary due to genetic polymorphism and so the results of the same exposure could be different.…”
Section: Pesticides As Endocrine Disrupting Chemicals (Edc)mentioning
confidence: 99%
“…Diethylstilbestrol is a synthetic estrogen. Prenatal exposure to diethylstilbestrol has been shown to increase the risk of cervical and vaginal cancer and pregnancy-related problems in women and testicular abnormalities in men (119). Diethylstilbestrol exposure in animals decreases promoter DNA methylation in reproductive tissues and increases methylation (and hence decreases activity) of DNMT (120).…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
“…Finally, it was taken off the market in 1971 subsequent to the elegant report by Herbset and coworkers who observed that in utero DES exposure has predisposed these girls "known as DES daughters" to develop an extremely rare type of cervicovaginal clear-cell adenocarcinoma (CCAC) at a young age (Herbst et al, 1971). In addition to a more than 100-fold increased risk of CCAC, DES daughters also suffered from increased incidences of vaginal dysplasia, vaginal and cervical adenosis, malformations of the cervix, vagina, and uterus, infertility and pregnancy complications (Rubin, 2007).…”
Section: Synthetic Estrogens: the Tragedy Of Diethylstilbestrol (Des)mentioning
confidence: 99%